The morphology of Chinese : a linguistic and cognitive approach - Packard, Jerome Lee, 1951- (Cambridge University Press, 2000)
Jerome Packard analyses the linguistic and cognitive nature of Chinese words, dispelling the common misconception that the Chinese language has no morphology. His ground-breaking study demonstrates how analysis of Chinese word formation enhances our understanding of the linguistic properties shared by all languages.